The Association Between Breast Milk Group B Streptococcal Capsular Antibody Levels and Late-onset Disease in Young Infants. (6th May 2019) - Dangor, Ziyaad; Khan, Mahtaab; Kwatra, Gaurav; Izu, Alane; Nakwa, Firdose; Ramdin, Tanusha; Fredericks, Joy; Lala, Sanjay G; Madhi, Shabir A
Abstract: Background: Animal-model studies have demonstrated less group B streptococcal (GBS) invasive disease and gastrointestinal colonization after enteral administration of serotype-specific capsular antibodies. There is, however, a paucity of information on the association of breast milk GBS serotype-specific capsular antibodies and risks for invasive disease in infants. The aim of this study was to explore the association between natural secretory immunoglobulin A (sIgA) capsular antibodies in breast milk and the occurrence of late-onset disease (LOD) in young infants. Methods: A matched case-control study was undertaken in infants <3 months of age in Johannesburg, South Africa. Breast milk samples were collected on cases and controls matched for gestational age, maternal age, and human immunodeficiency virus status at time of enrollment. Capsular serotype Ia, Ib, III, and V sIgA antibody concentrations were measured using the fluorescence-based micro-bead immunosorbent assay. Results: Breast milk samples were available for 31 LOD cases (8 serotype Ia and 23 serotype III), 21 recto-vaginally colonized matched controls (10 serotype Ia and 11 serotype III), and 84 serotype Ia and 105 serotype III noncolonized matched controls. Using a Bayesian model to estimate the probability of disease, there were 90% reductions in the risks of developing serotypes Ia and III LOD with sIgA concentrations ≥0.14 µg/mL and ≥2.52 µg/mL, respectively. Conclusions: Breast milk sIgA capsular antibodies were associated with lower risks for LOD in young infants. The ability of GBS polysaccharide-protein conjugate vaccines currently under development to induce sIgA responses warrant investigation as potential mediators of protection against LOD. Abstract : There was a 90% risk reduction of late-onset disease when young infants were fed breast milk with natural group B Streptococcus secretory immunoglobin A serotype Ia and III capsular antibody concentrations ≥0.14 µg/mL and ≥2.52 µg/mL, respectively